Ursus arctos Linnaeus 1758 - James H. Honacki; Kenneth E. Kinman; James W. Koeppl (Alien Press, Inc. & The Association of Systematics Collections, 1982)
Ursus arctos Linnaeus, 1758. Syst. Nat., 10th ed., 1:47. TYPE LOCALITY: Sweden. DISTRIBUTION: Formerly, N. W. Africa, all of Palearctic from W. Europe, Near and Middle East through N. Himalayas to W. and N. China and Chukotka (U.S. S.R.); Hokkaido (Japan). Western North America, north from N. Mexico. COMMENT: Hall, 1981:951- 958, listed 87 taxa (including 76 other species names) in the " Ursus arctos -group", which are here included in arctos; see Corbet and Hill, 1980:94; see also Couturier, 1954, L'Ours brun, Ursus arctos L., Grenoble. PROTECTED STATUS: CITES - Appendix II (all North American subspecies). CITES - Appendix I (Italian populations only). CITES - Appendix I as U. a. isabellinus subspecies only. CITES - Appendix I and U.S. ESA - Endangered as U. a. nelsoni subspecies only. CITES - Appendix I and U.S. ESA - Endangered as U. a. pruinosus subspecies only. U.S. ESA - Endangered as U. a. arctos (Italian populations only). U.S. ESA - Threatened as U. a. horribilis subspecies only. ISIS NUMBER: 5301412002006001001. Published as part of James H. Honacki, Kenneth E. Kinman & James W. Koeppl, 1982, Order Carnivora, pp. 244-289 in Mammal Species of the World (1 st Edition), Lawrence, Kansas, USA :Alien Press, Inc. & The Association of Systematics Collections on page 251, DOI: 10.5281/zenodo.7352980